Identity Creation and Retention of UGM as an Iconic Brand - Viklous, Belinda Ekharisti; Radjalewa, Cosmas Reynold; Sulistyowati (Deskripsi Bahasa, 2023)
This article aims to investigate how the iconicity of UGM is constructed, the underlying notion of UGM as an icon, and the reason behind the iconicity of UGM. The multiple interpretations of UGM as an icon are analyzed using Peirce's semiotic framework to show the relationship between the representamen, interpretant, and object. Blumer’s concept of symbolic interaction is also applied to display the interaction mechanism between the representamen and the interpretant on the formation of the iconic sign. And mixed methods are used as an approach to explain the data. As a result, this article has collected 168 tokens of interpretations of UGM with 5 dominant tokens explained, namely Berkualitas (Qualified), Jogja (Yogyakarta), Terbaik (The Best), Pintar (Smart), and Keren (Cool). The representamen and the interpretant are interrelated through bidirectional interpretations. UGM is projected as an iconic brand to serve identity creation and retention. Identity creation and retention might potentially promote social class and disparity as a result of power relations and distribution regarding UGM as an iconic brand. Further study needs to be conducted to address the issues. === Artikel ini bertujuan untuk mengkaji bagaimana ikonisitas UGM dikonstruksi, apa yang melatarbelakangi gagasan UGM sebagai ikon, dan alasan dibalik ikonisitas UGM. Multitafsir tentang UGM sebagai ikon dianalisis menggunakan kerangka semiotik Peirce untuk menunjukkan hubungan antara representamen, interpretant, dan objek. Konsep interaksi simbolik Blumer juga diterapkan untuk menampilkan mekanisme interaksi antara representamen dan interpretan pada pembentukan tanda ikonik. Dan metode campuran digunakan sebagai pendekatan untuk menjelaskan data. Hasilnya, artikel ini telah mengumpulkan 168 token interpretasi UGM dengan menjelaskan 5 token dominan, yaitu Berkualitas, Jogja, Terbaik, Pintar, dan Keren. Representamen dan interpretan saling terkait melalui interpretasi dua arah. UGM diproyeksikan sebagai merek ikonik untuk melayani penciptaan dan retensi identitas. Penciptaan dan retensi identitas berpotensi mengangkat kelas sosial dan disparitas akibat relasi kuasa dan distribusi yang menganggap UGM sebagai merek ikonik. Studi lebih lanjut perlu dilakukan untuk mengatasi masalah tersebut.